EFFECTIVENESS OF D-SALMA'S CATALOG SMART AS BEHAVIORAL CONTROL PREVENTION OF DENTAL CARIES IN PREGNANT WOMEN - Salmawati Salmawati; Suharyo Hadisaputro Suharyo Hadisaputro; Lanny Sunarjo Lanny Sunarjo; Bambang Sutomo Bambang Sutomo (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
Background:Pregnant women are one of the groups vulnerable to dental caries with a prevalence of 84.7%.During pregnancy, hormonal changes occur which are characterized by nausea, vomiting and feeling lazy about brushing teeth, the acidic nature and changes in saliva pH cause dental caries. This condition can result in low birth weight (LBW) babies, miscarriage and pre-eclampsia. One effort to improve the dental and oral health maintenance behavior of pregnant women is to carry out promotive and preventive measures using educational media. Objective:Producing appropriate educational models and analyzing their effectiveness in improving the behavior of pregnant women in preventing dental caries. Method: RD research type, quasy experiment method Pre-Posttest group design (nonequevalent control group design). In applying the model, a sample of 60 pregnant women was used, divided into 2 intervention groups with the development of the D-Salma's Catalog Smart model and a control group with a booklet. The variables measured are knowledge, attitudes and OHIS of pregnant women. Data analysis used univariate analysis, bivariate analysis and multivariate analysis. Results:The development of the D-Salma's Catalog Smart model is validated and suitable for application as a dental health education medium. The results of the effectiveness test increased knowledge from 3.40 to 8.00 (p=0.000), attitudes from 24.17 to 38.00 (p=0.000), actions from 12.77 to 28.00 (p=0.000), and reduced the OHIS score from 3.90 to 1.00 (p=0.000). Conclusion:The application of the development of the D-Salma's catalog smart model is feasible and effective in changing the behavior of pregnant women in preventing dental caries.